Oral History Interview: Martha Taylor (0775) - Lange, Robert; Taylor, Martha (My University, 2016)
Abstract: Childhood and early life in Madison; the influence of her grandfather, Professor Olaf Hougen; childhood years in Washington DC, Minneapolis, and Los Angeles; high school at a racially integrated school in Los Angeles; the student activist culture of the 1960s; undergraduate study at the University of California- Santa Barbara; transfer to the University of Wisconsin; degree in History; Master’s Degree at University of West Virginia; Employment at the UW Foundation in 1975; religious activities; the Bascom Hill Society; modernizing Foundation record keeping systems; Foundation publications and communication activities; Women’s philanthropy; the Women’s Philanthropy Council; workshops and seminars on women’s philanthropy, books; Campus leadership; the Foundation board and leadership; substantial gifts to the UW by women.
Interviewed by Robert Lange
Keywords: Lutheranism; Fundraising; Women in philanthropy; University of Wisconsin Foundation; Philanthropy